PENGARUH PENGAYAAN KERJA DAN KEPUASAN KERJA TERHADAP LOYALITAS GURU SMK SWASTA KECAMATAN KEBAYORAN BARU JAKARTA SELATAN - Zon Saroha Sitonga (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
The objective of this research is to understanding comprehensively the effect of job enrichment and job satisfaction on loyalty of vocational high school teacher in Kebayoran Baru sub district of South Jakarta. The research methodology is a survey method to form the causal path analysis. Research based on vocational high school teacher with total sample 135 teacher. The data analysis and interpretation indicator that (1) job enrichment has positive influence on loyalty (2) job satisfaction has positive inpleunce on loyalty (3) job enrichment has positive influence on job satisfaction.